Impact of movement tempo on bar velocity and time under tension in resistance exercises with different external loads - Trybulski, Robert; Gepfert, Mariola; Gawel, Dawid; Bichowska, Marta; Fostiak, Krzysztof; Wojdala, Grzegorz; Trybek, Grzegorz; Krzysztofik, Michal; Wilk, Michal (Biology of Sport, 2022)
The goal of the study was to determine the differences between volitional and maximal movement tempo during resistance exercise. Ten healthy men volunteered for the study (age = 26.4 ± 4.8 years; body mass  =  93.8  ±  9.6  kg; barbell squat one-repetition maximum (1RM)  =  175  ±  16.7  kg; bench press 1RM = 140.5 ± 26.8 kg). In a randomized order, the participants performed six sets of the barbell squat and the bench press exercise at progressive loads from 40% to 90%1RM (step by 10%) under two testing conditions: with volitional movement tempo or with maximal movement tempo. The three-way repeated measures ANOVA showed a statistically significant multi-interaction effect for time under tension (p < 0.001), peak bar velocity (p = 0.04) and for mean bar velocity (p < 0.001). There was also a statistically significant main effect of movement tempo for time under tension (p < 0.001), peak bar velocity (p < 0.001) and for mean bar velocity (p < 0.001). The post hoc analysis for main effect of tempo revealed that time under tension was significantly longer for volitional compared to maximal tempo (0.84 vs 0.67 s, respectively), peak bar velocity was significantly higher for maximal compared to volitional tempo (1.24 m/s vs 0.90 m/s, respectively), and mean bar velocity was significant higher for maximal compared to volitional tempo (0.84 m/s vs 0.67 m/s, respectively). The presented results indicate that there were significant differences between volitional and maximal movement tempos in time under tension and bar velocity (peak and mean), as well as significant differences in those variables between the two exercises. Therefore, the velocity of movement and time under tension is related to movement tempo, external load and type of exercise used.